Understanding the long‐term impact of the COVID‐19 pandemic on non‐muscle‐invasive bladder cancer outcomes: 12‐Month follow‐up data from the international, prospective COVIDSurg Cancer study - Cameron E. Alexander; Arjun Nathan; Alexander Light; Chuanyu Gao; Vinson Chan; Sinan Khadhouri; Kevin Gallagher; Kevin G. Byrnes; Michael Walters; Terry Hughes; Rita Perry; Kelvin Okoth; et al. (BJUI Compass)
Abstract Objective The objective of this study was to report the 12‐month oncological outcomes for patients with non‐muscle‐invasive bladder cancer (NMIBC) within the prospective, international COVIDSurg Cancer study. Patients and methods Eligible patients were aged ≥18 years and scheduled for elective surgical management of NMIBC with curative intent (transurethral resection of bladder tumour [TURBT] or bladder biopsy) from 21 January to 14 April 2020. The primary outcome was disease recurrence within 12 months of previous elective TURBT/bladder biopsy. Secondary outcomes included disease progression within 12 months of previous elective TURBT/bladder biopsy, site‐declared delay to surgery from diagnosis as a consequence of COVID‐19 and deviation in standard care due to COVID‐19. Comparisons were made to cohorts from the pre‐pandemic era. Results Bladder cancer accounted for 2.2% (n = 446) of patients in the COVIDSurg Cancer study, with data contributed by 27 centres across 12 countries internationally. Within this included cohort, 229 patients had NMIBC and 12‐month follow‐up data available. On application of National Institute for Health and Care Excellence (NICE) criteria, 47.2% were classified as having high‐risk disease. Overall disease recurrence and progression rates were 29.3% and 9.7% at 12 months, respectively. In purely high‐risk pre‐pandemic cohorts, the International Bladder Cancer Group (IBCG) estimates a recurrence rate of 25% at 12 months, and the European Association of Urology (EAU) NMIBC 2021 scoring model estimates a 12‐month progression rate of 3.5%. As a consequence of the COVID‐19 pandemic, 10.9% of patients had site‐declared delay to TURBT/bladder biopsy; 7.4% did not undergo intravesical therapy or had early discontinuation of this; 9.2% did not undergo early repeat resection for high‐risk disease; and 18.3% had a delay to cystoscopic follow‐up surveillance. Conclusions This prospective study indicates that there were widespread deviations in usual care for NMIBC during the pandemic and that 12‐month oncological outcomes appear to be impaired compared to published pre‐pandemic outcomes.